'Public on the outside, private on the inside': the organizational hybridization, sense of belonging and identity strategies of the employees of a public unemployment insurance fund in Switzerland. (March 2014) - Buffat, Aurélien
A number of studies show that New Public Management reforms have altered the current identity benchmarks of public officials, particularly by hybridizing values or management practices. However, existing studies have largely glossed over the sense of belonging of officials when their organization straddles the concerns of public service and private enterprise, so that the boundary between public and private sector is blurred. The purpose of this article is precisely to explore this sense of belonging in the context of organizational hybridization. It does so by drawing on the results of research conducted among the employees of a public unemployment insurance fund in Switzerland. On the one hand, the analysis shows how much their markers of belonging are hybrid, multiple and constructed in negative terms (with regard to the State), while indicating that the working practices of the employees point to an identity that is nevertheless closely bound with the public sector. On the other hand, the analysis shows that the organization plays strategically with its State status, by exploiting either its private or public identity in line with the needs related to its external image. The article concludes with a discussion of the results highlighting the strategic functionality of the hybrid identity of the actors. Points for practitioners: The article is of particular interest to practitioners who are questioning the effects on identity of the increasingly hybrid organizational context which organizations are faced with today – straddling a public service rationale and that of a private enterprise. While the organizational hybridity brought about by NPM is making matters increasingly complex for practitioners – especially with regard to the proliferation of expectations made of them – the article nevertheless notes that it is this very same hybridity that provides actors with multiple identity-related markers of belonging which practitioners are likely to exploit strategically to adapt to this growing spectrum of demands. The idea of playing alternately with the public or private identity of the organization according to context has the potential of giving an extra margin of manoeuvre to practitioners and managers working in a hybrid environment.